Genomic DNA Methylation in Diabetic Chronic Complications in Patients With Type 2 Diabetes Mellitus - Wang, Xixi; Yang, Wenhong; Zhu, Yunyan; Zhang, Shiyu; Jiang, Miao; Hu, Ji; Zhang, Hong-Hong (Frontiers in Endocrinology, 2022)
Aim: To explore the relationship between genomic DNA methylation and diabetic chronic complications. Methods: 299 patients with type 2 diabetes mellitus (T2DM) hospitalized in the Second Affiliated Hospital of Soochow University were enrolled. We divided the patients into different complications groups and corresponding non-complication groups. Clinical and biochemical parameters were compared between the two groups. The level of genomic DNA methylation in leukocytes was determined by high-performance liquid chromatography-tandem mass spectrometry. Results: (1) Age, duration of diabetes, creatinine (Cr), blood urea nitrogen (BUN), genomic DNA methylation, 24- hour urine total protein (24-hUTP), and intima-media thickness (IMT) were significantly higher in the carotid plaque (CP) group. Waist-to-hip ratio (WHR), body mass index (BMI), estimated glomerular- filtration rate (eGFR), and albumin (Alb) were significantly lower in the CP group. Gender, age and BMI were the influencing factors of CP. (2) Age, duration, Cr, BUN, urinary microalbumin creatinine ratio (UACR), systolic blood pressure (SBP), TCSS, and 24- hUTP were significantly higher in the diabetic retinopathy (DR) group. eGFR, 2h postprandial C- peptide, and Alb were lower in the DR group. Age, duration, Cr, Alb, SBP, and the presence of DN were the influencing factors of DR. (3) Age, duration, HbA1c, BUN, TCSS, SBP, and IMT(R) were significantly higher in the diabetic nephropathy (DN) group. 2h postprandial C-peptide, and Alb were lower in the DN group. HbA1c, BUN, DR, and HBP were the influencing factors of DN. (4) Age, duration, total cholesterol (TC), low-density lipoprotein (LDL-C), triglyceride (TG), Cr, BUN, uric acid (UA), and SBP were significantly higher in the diabetic peripheral neuropathy (DPN) group. The level of genomic DNA methylation and eGFR were significantly lower in the DPN group. Age, duration, LDL-C, UA, the presence of DR, and the genomic DNA methylation level were the influencing factors for DPN. Incorporating the level of genomic DNA methylation into the prediction model could improve the ability to predict DPN on the basis of conventional risk factors. Conclusion: Low level of genomic DNA methylation is a relatively specific risk factor for DPN in patients with T2DM and not a contributing factor to the other chronic complications.